Trustworthiness of Flexible Rockfall Protection Systems - Axel Volkwein; Marcel Fulde; Ingvar Krieger Hauksson (Geosciences, 2021)
Flexible rockfall protection systems are an effective and efficient remedy against rockfalls with energy levels between 100 and up to 10,000 kJ. Although they are heavily in use all around the world, the backgrounds that guarantee a reliable barrier are not well known by most of intervening agents and users. This contribution gives some insights on how to judge the capability, reliability, and trustworthiness of a rockfall protection system. The paper focuses on three strategies to build up confidence and trustworthiness regarding the barrier’s correct or expected functioning: testing, certification, and how to assess adaptions of standard barrier systems.